Telomere biology in the freshwater planarian Schmidtea mediterranea - Tan, Thomas Ching-Jen (2011)
Freshwater planarian Schmidtea mediterranea is an emerging model for studying in vivo gene functions and regulation in native cell niches. The obligate asexual strain of this species reproduces by fission, in which succession of soma occurs without passing through the germline. To achieve this somatic immortality the somatic stem cells need to overcome the end replication problem. Therefore it can be hypothesised that somatic telomere maintenance in asexual S. mediterranea must possess a germ-like property, with which age-related erosions can be adequately repaired. In this PhD project, the telomere repeat unit in S. mediterranea was confirmed to be the vertebrate-like TTAGGG. Attrition of whole body telomere length was found in ageing sexual worms and also in asexual worms which had not gone through recent fission events. Opposite telomere length dynamics were observed in regenerated samples of the two strains, with erosion in the sexuals and reset in the asexuals. The telomere maintenance was found to increase during regeneration in both strains, with a higher level of increase in asexual worms. A homolog of the telomerase reverse transcriptase subunit, Smed_Tert, was identified and characterised in this organism. High level of Smed_Tert expression was seen in germ cells in mature sexual worms and adult stem cells in asexual worms. Knockdown of Smed_Tert expression by RNA interference caused progressive telomere erosion, however effects on cell proliferation and viability have not been observed in knockdown samples. Four alternate splice isoforms of Smed_Tert were identified. The enhanced telomerase activity during regeneration correlates with a proportional increase in the full-length isoform and a decrease in isoforms with a truncated TRBD domain, suggesting a dominant negative regulation of telomerase by alternative splicing. Significant increase in the expression of the full-length isoform was seen in regenerating asexual samples but not in sexual strains, which correlates with their telomere length dynamics. It is hoped that the comparative studies between the sexual and asexual strains can improve our understanding of how soma can evolve to become an effective inheritable unit.